A Meta-Analysis of The Experiences and Impacts af Discrimination Against Muslim Communities In Various Countries: Focus on Psychological and Social Aspects - Pasaribu, Ahmad Muchlisin Natas; Nasution, Satri Dwi Kurnia; Rahmaniar, Yusi (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
Discrimination against Muslim communities is a persistent global phenomenon with significant implications for individual well-being and social cohesion. This study aims to systematically synthesise empirical evidence on the experiences of discrimination faced by Muslim communities in different countries and analyse its impact on psychological, social and economic aspects. Using a meta-analysis approach, this study collected and analysed data from relevant quantitative studies published between 2020 and 2024, which were identified through comprehensive searches on electronic databases such as Scopus, Web of Science, PsycINFO, and PubMed, as well as manual searches. Strict inclusion criteria were applied to ensure the quality and relevance of the studies. Pooled effect sizes will be calculated using random-effects models to estimate the prevalence of different forms of discrimination (e.g., in the workplace, education, public spaces) and the magnitude of their impact (e.g., on mental health, identity, social participation). Heterogeneity analyses and subgroup analyses will be conducted to explore variation in findings across geographic contexts and other study characteristics. The results of this meta-analysis are expected to provide a comprehensive picture of the scale and manifestation of discrimination against Muslims, as well as its scientifically documented impact. The conclusions of this study will highlight important implications for the development of more effective anti-discrimination policies, intervention programmes, as well as future research agendas to promote equality and inclusion for the global Muslim community. Recommendations from this study emphasise the urgency for policymakers to strengthen anti-discrimination laws and enforcement mechanisms, for educators and practitioners to design culturally sensitive interventions that support Muslim communities, and for researchers to expand cross-regional studies that can capture underrepresented contexts. These actions are expected to foster inclusivity, reduce prejudice, and enhance the resilience and well-being of Muslim individuals and communities worldwide.